Immobilization strategies and analytical applications for metallic and metal-oxide nanomaterials on surfaces - Pena-Pereira, Francisco (2019)
In this work, we provide an overview of the different strategies employed for achieving the immobilization of metallic and metal-oxide nanomaterials on solid substrates for analytical purposes. We describe significant strategies employed for obtaining solid surfaces with attached metallic nanoparticles (MNPs), and report on surfaces used for immobilization of MNPs, and their characteristics. Finally, we discuss representative applications of metallic and metal-oxide nanomaterials in different areas of analytical chemistry (localized surface-plasmon-resonance sensors, surface-enhanced Raman scattering substrates, electrochemistry, microextraction coatings, analytical separations, and quartz-crystal-microbalance sensors).